Influence of fecal fermentation on the anthelmintic activity of proanthocyanidins and ellagitannins against human intestinal nematodes and Caenorhabditis elegans - Jato, Jonathan; Orman, Emmanuel; Boakye, Yaw Duah; Belga, François Ngnodandi; Ndjonka, Dieudonné; Oppong Bekoe, Emelia; Liebau, Eva; Spiegler, Verena; Hensel, Andreas; Agyare, Christian (Frontiers in Pharmacology, 2024)
Some tannin-rich plants such as Combretum mucronatum and Phyllanthus urinaria are widely used in Africa for the control of parasitic nematodes in both humans and livestock. Tannins have been recognized as an alternative source of anthelmintic therapies and hence recent studies have focused on both the hydrolysable and condensed tannins. These groups of compounds however have poor oral bioavailability and are metabolized by gut microbiota into lower molecular weight compounds. The role of these metabolites in the anthelmintic activities of tannins has not yet been explored. This study investigated effects of fecal metabolism on the anthelmintic potential of procyanidin C1 (PC1) and geraniin, and tannin-enriched extracts of C. mucronatum and P. urinaria (PUH) which contain these compounds, respectively. Metabolites were formed by anaerobic fermentation of the test compounds and extracts in a fresh human fecal suspension for 0 h, 4 h and 24 h. Lyophilized samples were tested in vitro against hookworm larvae and whipworm larvae obtained from naturally infected human populations in Pru West District, Ghana and against Caenorhabditis elegans (L4). Extracts and compounds in undegraded state exhibited a concentration-dependent inhibition of nematodes. Their activity significantly decreased upon fecal metabolism. Without fermentation, the proanthocyanidin-rich CML extract was lethal against hookworm L3 (LC50=343.5 µg/mL, 95% confidence interval (CI)=267.5 -445.4), T. trichiura L1 (LC50=230.1 µg/mL, CI=198.9-271.2), and C. elegans (LC50=1468.1 µg/mL, CI=990.3 -1946.5). PUH from which the ellagitannin, geraniin, was isolated, exhibited anthelmintic effects in the unfermented form with LC50 of 300.8 µg/mL (CI = 245.1 -374.8) against hookworm L3, LC50 of 331.6 µg/mL (CI = 290.3 -382.5) against T. trichiura L1, but no significant activity against C. elegans L4 larvae at the tested concentrations. Similarly, both compounds, procyanidin C1 and geraniin, lost their activity when metabolized in fecal matter. The activity of geraniin at a concentration of 170 µg/mL against C. elegans significantly declined from 30.4 ± 1.8% to 14.5 ± 1.5% when metabolized for 4 h whereas that of PC1 decreased from 32.4 ± 2.3% to 8.9 ± 0.9% with similar treatment. There was no significant difference between the anthelmintic actions of metabolites from the structurally different tannin groups.